The Effect of Learning Motivation on Junior High School Students’ Mathematical Representation Ability - Rizal Maulana Darmawan; Mulyono (Universitas Negeri Semarang, 2026)
This study aims to examine the effect of learning motivation on junior high school students’ mathematical representation ability. This research employed a quantitative approach using a survey method. The population of this study consisted of all seventh-grade students at SMP Negeri 13 Semarang in the 2025/2026 academic year, with a sample of 30 students selected through cluster random sampling. The research instruments included a mathematical representation ability test and a learning motivation questionnaire. The data were analyzed using normality and linearity tests, followed by a simple linear regression test. The results showed that learning motivation has a positive and significant effect on students’ mathematical representation ability, as indicated by a significance value of 0.000 (< 0.05). The coefficient of determination (R²) was 0.486, meaning that learning motivation contributes 48.6% to students’ mathematical representation ability. This finding suggests that students with higher learning motivation tend to have better ability in representing mathematical ideas through various forms of representation. In conclusion, learning motivation plays an important role in improving students’ mathematical representation ability. Therefore, teachers are encouraged to enhance students’ motivation in order to support better mathematics learning outcomes.